The mediating effects of school bullying victimization in the relationship between childhood trauma and NSSI among adolescents with mood disorders - Yue Liu; Xueqian Xu; Xiaodan Huang; Qingxiao Hong; Longhui Li; Xiaohu Xie; Weisheng Chen; Wenwen Shen; Huifen Liu; Zhenyu Hu (BMC, 2024)
Abstract Background Nonsuicidal self-injury (NSSI) is a serious problem in the adolescent population worldwide. Childhood trauma and bullying have been identified as risk factors for NSSI. We explored the relationships among Childhood trauma, Bullying victimization and the severity of NSSI behaviours, and test the effect of Bullying victimization in mediating the association between Childhood trauma and the NSSI behaviours. Methods A total of 123 adolescents were recruited. They were diagnosed with depression or depressive episodes of bipolar disorder and had experienced NSSI in the last year. They were assessed using the Chinese version of the Childhood Trauma Questionnaire (CTQ-C), the Revised Olweus Bullying Victimization Questionnaire (OBVQ-R), and the Adolescent Self-Harm Questionnaire (ASHQ). Results Females presented a significantly greater prevalence of sexual abuse and relationship bullying than boys. Individuals in the younger age group (10-14 years) presented a greater incidence of emotional neglect, verbal bullying, relationship bullying, and total bullying, and their NSSI score was also higher than that of those in the older age group (15-19 years). Only children show a greater prevalence of sexual abuse than nononly children. Single-parent families scored higher on emotional abuse, emotional neglect, physical neglect and physical bullying than two-parent families. There was a significant positive correlation between each dimension of childhood trauma and all the dimensions of bullying, between childhood trauma and NSSI, and between bullying and NSSI. Childhood trauma can not only directly affect the severity of NSSI but also indirectly aggravate the severity of NSSI through bullying victimization. The mediating effects of bullying victimization on emotional abuse, physical abuse, emotional neglect and physical neglect were 14%, 21%, 20%, 13% and 20%, respectively. Conclusion There was a significant positive correlation between childhood trauma and bullying, between childhood trauma and NSSI, and between bullying and NSSI. Childhood trauma can not only directly affect the severity of NSSI but also indirectly aggravate the severity of NSSI through bullying victimization. Bullying victimization played the partial mediating effects between Childhood trauma and NSSI.